Optimisation of Bioethanol Production in a Potato Processing Industry - Vassilios Felekis; Chrysanthi Stavraki; Dimitris Malamis; Sofia Mai; Elli Maria Barampouti (Fermentation, 2023)
Nowadays, there is a requirement for industries to eliminate carbon from their energy mix and substitute it with greener options. This calls for investment in efforts to facilitate the scaling up of technical advancements. Because of the huge amount of waste, a life cycle strategy has been used by industries, especially the food industry, to lessen the environmental impact of their products. One of the sectors that burdens the environment with a significant amount of waste is the potato processing industrial sector. The current study focuses on the valorisation of all the potato processing waste streams (potato peels, potato tubers and slices, starch and low-quality chips) towards bioethanol production at a pilot level. After their physico-chemical characterisations, several experimental trials were performed in order to determine the optimum pretreatment and hydrolysis conditions for each waste stream. Acid hydrolysis, alkaline hydrolysis and hydrothermal pretreatment were examined when no pretreatment resulted in low ethanol yields (below 60%). The optimum results that were obtained were applied in a pilot plant of 200L to examine the upscaling factor. It was verified that upscaling by 1000 times generates comparable and, in some cases, greater results. From the integration of the results and the mass balances of a typical potato processing company, a full-scale implementation plan was also set up, where it was calculated that around 2 m3 bioethanol per week could be produced.